Literature Study: Liveworksheet as a Science Learning Media Electronic Student Worksheet in The Merdeka Curriculum - Novike Bela Sumanik; Lamtiar Ferawaty Siregar; Yenni Pintauli Pasaribu; Yorinda Buyang (Technium Social Sciences Journal, 2023)
Liveworksheet is a web-based application that can be used in the merdeka curriculum. The use of technology in the merdeka curriculum is very necessary because requires liberating teachers and students in exploring information. The purpose of this research is to examine the use of liveworksheets as an innovative electronic student worksheet learning media in the merdeka curriculum. This research is descriptive research with a literature review. The liveworksheets platform is a learning medium that can be used at all levels of education and in all subjects. The forms of questions in liveworksheets are varied, namely multiple choice, essay, join arrow, drop-down, drag and drop, check box, word search, listening and speaking, this is what makes the liveworksheet have an attractive appearance like an educational game so that it can give a new feel that is not boring. The use of liveworksheets has many benefits including making students more challenged and active thereby increasing learning motivation. This increase in motivation has an impact on student learning outcomes. The effectiveness of using liveworksheets has been widely studied so that the use of liveworksheets can be used in the learning process, especially in the era of independent learning.